PENUNDAAN PEMBAYARAN UPAH PEKERJA - Ramadana, Sri Winarsih; Rahmaniar, Rahmaniar (Prodi Hukum Ekonomi Syariah, STI Syariah AL-Hilal SIgli, 2023)
Delays in the payment of wages can occur in several situations, for example, when the shop owner is experiencing financial problems or when events disrupt the grocery store's operation. However, delaying the payment of wages without a valid reason and the employees' consent may violate labor laws. It may negatively affect the relationship between the grocery store owner and the employees. Suppose a grocery store is experiencing financial problems and cannot pay wages on time. In that case, it should clearly and transparently inform employees of the situation and provide assurances that wages will be delivered as soon as possible. Grocery stores must also make efforts to find appropriate solutions, such as finding funding sources or carrying out financial restructuring to pay employee wages on time. The research aims to look at the practice of delaying the payment of workers' salaries in Sigli City. The research method that the author uses in this research is descriptive analysis, with the research approach used in this research being qualitative. The results showed that the Cahaya Family grocery store never experienced delays in salary payments. Still, there were also delays in salary payments because there were workers who were allowed to go home during the day. Only at H. Nurdin's grocery store where the salary payment was late, and the reason for the transaction needed to be explained in detail.